2020
DOI: 10.1002/slct.202003812
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Cu2O@g‐C3N4: Recyclable Photocatalyst under Visible Light to Access 2‐Aryl‐/benzimidazoles/benzothiazoles in Water

Abstract: An unprecedented Cu/Cu2O@g‐C3N4 catalysed visible light driven green synthesis of 2‐aryl‐/benzimidazoles and benzothiazoles is reported via condensation of structurally different aldehydes with o‐phenylenediamine and o‐aminothiophenol respectively. Herein, Synergistic catalysis is operating as both Cu/Cu2O@g‐C3N4 and visible‐light condition are required, no product was isolated in absence of either. Operational simplicity, ambient reaction conditions, aqueous medium, good yield of products (80–94 %) and recycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Most of the results suggested that the photocatalytic conversion process was well compatible with the substituents no matter they are electron‐withdrawing or ‐releasing groups, such as −OH, −Cl, −Br, −NO 2 . They had little effect on the yield of BIs [15,37,43] . Some other studies showed that the activity of aromatic aldehydes with electrophilic substituents was slightly higher than that with electron‐donating substituents [16–17,23,42] .…”
Section: The Effect Of Reaction Conditions On the Yield Of Bismentioning
confidence: 94%
See 4 more Smart Citations
“…Most of the results suggested that the photocatalytic conversion process was well compatible with the substituents no matter they are electron‐withdrawing or ‐releasing groups, such as −OH, −Cl, −Br, −NO 2 . They had little effect on the yield of BIs [15,37,43] . Some other studies showed that the activity of aromatic aldehydes with electrophilic substituents was slightly higher than that with electron‐donating substituents [16–17,23,42] .…”
Section: The Effect Of Reaction Conditions On the Yield Of Bismentioning
confidence: 94%
“…The high activity observed in MeCN may ascribe to the stabilization of the photoinduced radicals by MeCN. In addition, Singh's work [43] indicated that the yield of BIs was proportional to the polarity of the solvent and decreased in order of water> ethanol> MeCN. The reaction performed in non‐polar toluene showed no yield of BIs.…”
Section: The Effect Of Reaction Conditions On the Yield Of Bismentioning
confidence: 99%
See 3 more Smart Citations